The invisible mistakecase - Harper, Charise Mericle (Boston : Houghton Mifflin, 2005)
After calling her friend "big pink baby," Charlotte, a young alligator, feels terrible until Grandpa tells her about a useful way to learn from her mistakes.
Keywords: Alligators -- Fiction; Conduct of life -- Fiction; Grandfathers -- Fiction; Alligators -- Juvenile fiction; Conduct of life -- Juvenile fiction; Grandfathers -- Juvenile fiction